THE USE OF MAPLE MATHEMATICAL SOFTWARE IN TEACHING MEDICAL AND BIOLOGICAL PHYSICS - H. Yu. Morokhovets; M. S. Saienko; Yu. V. Lysanets; O. V. Silkova (Проблеми екології та медицини)
Computerization of training becomes an integral part of the educational process. The development of technologies, mobile devices necessitates the improvement and updating of training courses. The use of software in the learning process is widespread, which requires from a modern student to master the mathematical apparatus, to have knowledge of the basics of programming and the ability to work at the level of a confident user with a variety of software tools and applications. Particularly relevant is the need for the use of computer technologies during the study of topics for self-directed study. The introduction of information technologies will enrich the content and diversify the ways of mastering new topics, stimulating students for self-education and self-development. The article is devoted to application of the software package of applied mathematics Maple during the educational process of students of higher medical establishments.